Readings in Social Theory The classic tradition to post-modernism - Farganis, James (Boston The McGraw-Hill, 2014)
Presenting an anthology of primary readings in sociological theory, this book covers the theorists and schools from classic to contemporary, modernist, and postmodernist, in a chronological organization. It is useful for professors who want to encourage students to read and interpret original sources.
Keywords: Sociology -- Philosophy